Interplay between spin frustration and magnetism in the exactly solved two-leg mixed spin ladder - 齐岩 吕松玮 杜安 于乃森 (Chinese physics B, 2016)
We study a mixed spin-（3/2,1） ladder system with antiferromagnetic rung coupling and next-nearest-neighbor interaction.The exactly solved Ising-chain model is employed to investigate the ground-state properties and thermodynamics of the low-dimensional ladder system.Our results show that the competition between different exchange couplings brings in a large variety of ground states characterized by various values of normalized magnetization equal to 0,1/5,2/5,3/5,1.Moreover,an interesting double-peak structure is also detected in the thermal dependence of magnetic susceptibility and specific heat when the frustration comes into play.It is shown that the double-peak phenomenon at zero-field for the case of AF2 ground-state arises from the very strong antiferromagnetic rung coupling,while other cases are attributed to the excitations induced by temperature and external field around the phase boundary.